1985
DOI: 10.1002/qj.49711147006
|View full text |Cite
|
Sign up to set email alerts
|

Ozone photochemistry in the antarctic stratosphere in summer

Abstract: Ozone photochemistry over Antarctica in summer has been examined using a 1-D model. With diffusive transport alone, the predicted ozone decay rates from the December (summer) solstice to the March (autumn) equinox were found greatly to exceed observed rates. In order to obtain broad agreement between calculated and observed ozone amounts, it was necessary to include the effects of a slow downward mean velocity. The velocities used, a few tens of metres per day. are compatible with a Lagrangian mean circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 12 publications
1
29
0
1
Order By: Relevance
“…The rapid ozone depletion in the spring, caused by heterogeneous chemical reactions, results in significant ozone loss at around 70 hPa in October, with the depletion up to 98 % compared to the early 1970s period as observed over South Pole and Syowa stations (S. Solomon et al, 2005). The lowest total ozone concentration and the area of the Antarctic ozone hole, however, vary from year to year (Douglass et al, 2011). In 2002 the unique dynamical situation resulted in the first sudden stratospheric warming ever observed in the Southern Hemisphere (Newman and Nash, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid ozone depletion in the spring, caused by heterogeneous chemical reactions, results in significant ozone loss at around 70 hPa in October, with the depletion up to 98 % compared to the early 1970s period as observed over South Pole and Syowa stations (S. Solomon et al, 2005). The lowest total ozone concentration and the area of the Antarctic ozone hole, however, vary from year to year (Douglass et al, 2011). In 2002 the unique dynamical situation resulted in the first sudden stratospheric warming ever observed in the Southern Hemisphere (Newman and Nash, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the middle of the 1980s, when the Antarctic ozone hole was first discovered (Farman et al, 1985), severe ozone depletion has been observed every austral spring over the Antarctic region (Douglass et al, 2011). The levels of ozone depleting substances (ODSs) and the specific meteorological conditions control the development of the seasonal Antarctic ozone hole (Montzka et al, 2011;Douglass et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone concentrations in late summer are close to chemical equilibrium, which results from the balance of ozone production (governed by O 2 photolysis) and loss (Fahey and Ravishankara, 1999;Fahey et al, 2000). At these altitudes and under polar summer conditions, the loss is dominated by chemistry involving NO x species, which are present at high concentrations since high amounts of NO y subsided into the polar middle stratosphere during the preceding winter and these are efficiently converted into NO x during polar day in summer (Farman et al, 1985;Fahey and Ravishankara, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In the summer, lower ozone has also been noted inside anticyclones, but is typically attributed to dynamics instead of chemistry Orsolini and Nikulin, 2006). Overall, summertime ozone loss is driven by 24-h sunlight, as NO x is released from its night-time reservoirs, leading to a ∼ 30 % decrease in the ozone column (e.g., Farman et al, 1985;Perliski et al, 1989;Fahey and Ravishankara, 1999).…”
Section: Introductionmentioning
confidence: 99%